bahasa indonesia : bahasa inggris - Silmi Mursidah; Yenni Samri Juliati Nasution; Laylan Syafina (Yayasan Pendidikan Penelitian Pengabdian Algero, 2023)
This study aims to determine the accountability of the PTPN II Ubudiyah Aulawiyah Mosque, the Al-Ikhlas Mosque, the Shalatul Falah Mosque in Tanjung Morawa District, to find out the application of financial reports to the PTPN II Ubudiyah Aulawiyah Mosque, the Al-Ikhlas Mosque, the Shalatul Falah Mosque in Tanjung Morawa District with ISAK 35, to find out the factors that hinder the accountability of the PTPN II Ubudiyah Aulawiyah Mosque, the Al-Ikhlas Mosque, the Salahul Falah Mosque in Tanjung Morawa District. The method used in this study is a qualitative method with a descriptive approach. The subjects in this study were the chairman and treasurer of the mosque and the objects of this research were the recording and financial reports of the three mosques. Data collection uses primary and secondary data from interviews, observation, and documentation. The results of this study indicate that the administrators of the PTPN II Ubudiyah Aulawiyah mosque, Al-Ikhlas Mosque, and the Shalatul Falah Mosque have recorded and reported well, although they are still simple, only limited to recording the income and expenses of the mosque. The application of ISAK 35 regarding the presentation of financial statements of non-profit oriented entities in this case the mosque has not been implemented at the Ubudiyah Aulawiyah PTPN II mosque, Al-Ikhlas Mosque, Shalatul Falah Mosque. Because the treasurer of the mosque admits that the term is foreign to them. And the obstacles in preparing financial reports based on ISAK 35 faced by the management of the Ubudiyah Aulawiyah PTPN II mosque were the limited time in preparing financial reports, the Al-Ikhlas mosque had problems understanding ISAK 35 due to a lack of outreach to administrators, and the Shalatul Falah mosque was aware of the weakness of human resources in accounting.